Between Relevance Systems and Typification Structures: Alfred schutz on Habitual Possessions - Tomas da Costa (Phenomenology and Mind, 2016)
Alfred Schutz’s characterization of the interrelationship between relevances and typifications includes an analysis of the phenomenon of habit that, in his theory of knowledge, clarifies some essential aspects of common-sense interpretations in the reality of daily life. In form of “habitual possessions”, habit becomes in Schutz an element of knowledge, is characterized as a potential set of typical expectations to be actualized under typical circumstances. In this article, the constitution process of habitual possessions are analyzed considering its place in the interplay between relevance systems and typification structures in common-sense thinking – by pointing out that, for Schutz, habitual possessions must always be understood as habitual possessions of knowledge.